PERILAKU PENYALAHGUNAAN MINUMAN KERAS DI KALANGAN REMAJA DI DESA SULUAN KECAMATAN TOMBULU KABUPATEN MINAHASA - Mira Silvana Tampomalu; Ferdinand Kerebungu; A.R. Umaternate (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
The objectives to be achieved in this study are to examine the behavior of alcohol abuse and to describe the factors that influence adolescents to consume alcohol among adolescents in Suluan Village, Tombulu District. The focus of the research in this study is "Alcohol Abuse Behavior Among Adolescents in Suluan Village, Tombulu District, Minahasa Regency. The research method used is qualitative. Qualitative research method aims to provide a systematic, factual and accurate description. Data collection techniques are observation, interviews and documentation. The behavior of alcohol abuse among teenagers in Suluan Village It is very severe and disturbing the people in the village, sometimes they even create problems in the midst of the community, namely by fighting, even holding people who pass on the street, if they have consumed alcohol. liquor the ability to control themselves both physically and socially is out of control. Teenagers roam the streets screaming, it makes the local community very disturbed by their actions. The behavior of teenagers every day in Suluan Village, most of them consume liquor to get drunk. Some even consume liquor for a full day and when they get drunk they can no longer control themselves because their emotions are disturbed. The objectives to be achieved in this study are to examine the behavior of alcohol abuse and to describe the factors that influence adolescents to consume alcohol among adolescents in Suluan Village, Tombulu District. The focus of the research in this study is "Alcohol Abuse Behavior Among Adolescents in Suluan Village, Tombulu District, Minahasa Regency. The research method used is qualitative. Qualitative research method aims to provide a systematic, factual and accurate description. Data collection techniques are observation, interviews and documentation. The behavior of alcohol abuse among teenagers in Suluan Village It is very severe and disturbing the people in the village, sometimes they even create problems in the midst of the community, namely by fighting, even holding people who pass on the street, if they have consumed alcohol. liquor the ability to control themselves both physically and socially is out of control. Teenagers roam the streets screaming, it makes the local community very disturbed by their actions. The behavior of teenagers every day in Suluan Village, most of them consume liquor to get drunk. Some even consume liquor for a full day and when they get drunk they can no longer control themselves because their emotions are disturbed.